Overlapping measures or constructs? An empirical study of the overlap between self-control, psychopathy, Machiavellianism and narcissism - DeLisi, Matt (2021)
Overlap between self-control and dark triad traits (i.e., psychopathy, Machiavellianism, and narcissism) is potentially problematic for efforts to distinguish dimensions associated with elevated risk for antisociality and crime. The aim of the present study is to examine the potential overlap between self-control and psychopathy, Machiavellianism, and narcissism, with a focus on the Brief Self-Control Scale (BSCS) and the Dirty Dozen Dark Triad scale (DD). The sample consisted of 567 youth (M = 15.91 years, SD = 0.99 years, age range = 14-18 years) from Portugal. Exploratory and confirmatory factor analysis results from the pooled set of items of the BSCS and the DD measures revealed that both are valid and reliable measures of their respective constructs. However, consistent with previous research, the narcissism facet of the DD emerged as an independent factor. Our findings suggest that if such an eventual overlap is detected, it would be a question of problematic measures, not constructs.